On the time response determination of condensation particle counters. Issue 7 (3rd July 2018) - Enroth, Joonas; Kangasluoma, Juha; Korhonen, Frans; Hering, Susanne; Picard, David; Lewis, Greg; Attoui, Michel; Petäjä, Tuukka
ABSTRACT: Condensation particle counter (CPC) technology has continued to evolve, with the introduction of several new instruments over the last several years. An important aspect in the characterization of these instruments is the measurement of their time response. Yet there is no standardly accepted approach for this measurement. Here we evaluate different classically used methods for determining CPC time response, and present the potential pitfalls associated with these approaches. Further, we introduce a new simple definition for the term response time, ϵ, which is based on the first-order systems response, while providing a practical definition by corresponding to ∼95% change in concentration. We also present results for various commonly used CPCs, and for the Airmodus A11 nano Condensation Nucleus Counter (nCNC) system, the TSI 3777+3772 Nano Enhancer system, and Aerosol Dynamics Inc.'s (ADI) new versatile water condensation particle counter. Copyright © 2018 American Association for Aerosol Research